Perfile dinâmica do emprego em telecomunicaç\~oes no Brasil entre 1998 e 2011 - Rodrigo Abdalla Filgueiras de Sousa; Paulo A. Meyer M. Nascimento (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This study explores three issues related to the job market in the Brazilian information and communication technologies (ICT) industry, considering both industrial and service segments. First of all, evolution of job structure in the sector is evaluated since 1998. Second, the intensity of Science, Technology, Engineering & Mathematics (STEM) personnel is measured in order to analyze the sector's potential in innovation within Brazilian Economy. Third, it discusses to which extent the availability of STEM workforce should (or not) be regarded as a growth restriction for the Brazilian ICT sector. Results point out that ICT employees are younger, better educated and earn more han their peers employed in other sectors of the Brazilian economy. Besides, results also unveil a higher proportion of STEM jobs in the ICT sector than the national average. Differently from the world scenario, these trends are more expressive in the service segment than in the industrial segment of ICT sector. Even demanding relatively more STEM professionals than the Brazilian average, ICT firms do not seem to face a long term shortage of such professionals between 1998 and 2009; nevertheless, under a short term analysis, data suggest a temporary disequilibrium in two specific moments: January-September 2008 and July 2010 onwards. Data also reveal possible weaknesses in the execution of RD&I projects, due to high rates of worker turnover and low rates of net job creation among STEM careers.
Keywords: L96; J21; O30; J63; 330; telecomunications; workforce; STEM personnel shortage; Telekommunikationssektor; Erwerbstätigkeit; Arbeitskräfte; Brasilien